2011
DOI: 10.1103/physrevlett.106.201601
|View full text |Cite
|
Sign up to set email alerts
|

Entanglement of Low-Energy Excitations in Conformal Field Theory

Abstract: In a quantum critical chain, the scaling regime of the energy and momentum of the ground state and low lying excitations are described by conformal field theory (CFT). The same holds true for the von Neumann and Rényi entropies of the ground state, which display a universal logarithmic behaviour depending on the central charge. In this letter we generalize this result to those excited states of the chain that correspond to primary fields in CFT. It is shown that the n-th Rényi entropy is related to a 2n-point … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

16
326
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 188 publications
(342 citation statements)
references
References 23 publications
16
326
0
Order By: Relevance
“…In Ref. [46] it has been shown that the entanglement entropies of low-lying excited states display a universal finite size scaling that is different from the one in the ground state of Eq. (3).…”
Section: Excited States In Periodic Chainsmentioning
confidence: 99%
“…In Ref. [46] it has been shown that the entanglement entropies of low-lying excited states display a universal finite size scaling that is different from the one in the ground state of Eq. (3).…”
Section: Excited States In Periodic Chainsmentioning
confidence: 99%
“…[5,6] for some results in various CFT setups and Ref. [7] for entanglement in a related class of globally excited states. In 2d CFT this analysis can be preformed analytically and Rényi entropies detect an increase in entanglement equal to the logarithm of the quantum dimension of the conformal family [8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…In 2D rational CFTs, it was found [15] that for the locally primary excited states, the Rényi entropy difference is related to the quantum dimension [5][6][7][8][9] of the primary operator, which is a kind of topological quantity. The computations of the entanglement entropies for locally excited states have been formulated in [10][11][12] in the field theory side. The entanglement entropy for local free scalar have…”
Section: Introductionmentioning
confidence: 99%